222 OLDER ADULT INPATIENTS' PERCEPTIONS OF PROGRESSIVE RESISTANCE TRAINING IN A SPECIALIST GERIATRIC REHABILITATION SETTING. (18th November 2021) - Burke, C; O'Neill, E; Timmons, S; Kurian, S; Mello, S; Fitzgerald, M
Abstract: Background: Progressive resistance training (PRT) has the potential to reduce age-related disability and has been proven to benefit the older adult in a variety of ways. PRT is prescribed routinely by physiotherapists for frail older adults in an inpatient setting. To date little is known of their experiences engaging in PRT. This study aimed to explore older adult inpatients' perceptions and experience of PRT as part of their overall physiotherapy program in a Specialised Geriatric Rehabilitation Unit. Methods: The study had a qualitative design. Semi-structured interviews explored experiences and perceptions of PRT along with motivators and barriers to participation. Interviews were face to face and conducted in the unit. Data was analysed using thematic analysis. 11 frail older inpatients with orthogeriatric (n = 5), neurological (n = 2), general surgical (n = 2) and general medical (n = 2) diagnoses were interviewed. Results: The study identified three overarching themes: Acceptability, Facilitators and Barriers. In the category of Acceptability participants identified the subthemes: (1) PRT is challenging, (2) PRT is Rewarding and (3) PRT is Enjoyable. In the category of Facilitators, the following subthemes emerged: (4) Positive outcomes as motivators and (5) Supervision is necessary for engagement. In the category of Barriers, (6) Low self-efficacy beliefs and (7) the Negative effects of PRT, such as pain and fatigue affected participation . Conclusion: Frail older inpatients find PRT to be an acceptable form of exercise. It is perceived to be challenging, but rewarding and enjoyable for most. Participants were motivated to participate in PRT by the positive outcomes (improved strength, general health, function, independence, confidence) they experienced. They felt supervision from professionals with medical expertise was essential to participation; and had low self-efficacy beliefs surrounding independent practice; fearing falling and causing harm. Pain and fatigue also impacted participation.